Urgensi Penguatan Nilai Integritas dalam Pendidikan Karakter Siswa - Laros Tuhuteru; Deisye Supit; Mulyadi Mulyadi; Ayi Abdurahman; Mohammad Syahru Assabana (Departement of Mathematics Education, 2023)
This study aims to evaluate the importance of strengthening the value of integrity in student character education. The study method used is literature study with a philosophical approach or content analysis. An important finding in this paper is that character education programs need to be improved to address the moral and character problems that exist in Indonesia today. Even though there has been a character education program in the national education system, there are still many cases that do not meet expectations. This is due to the design of the program that does not cover all actors and does not touch on mindset and operational strategy aspects. Character education is impressed as a student's obligation and only focuses on conscious and cognitive thinking. Therefore, character education, especially the value of integrity, must continue to be applied by school principals and teachers through various programs that are structured and have goals for students